Analisis Penentuan Platform E-Commerce Menggunakan Metode SAW Berdasarkan Kepuasan Pelanggan pada Gerai Taslim - Ari Setiawan; Sri Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of e-commerce has encouraged retail businesses to utilize various digital platforms to increase sales and customer satisfaction. Gerai Taslim, a Muslim fashion retailer, uses Shopee, Tokopedia, and Lazada as online sales media, but does not yet have a structured analysis to determine the most optimal platform. This study aims to determine the best e-commerce platform based on customer satisfaction levels using the Simple Additive Weighting (SAW) method. The study uses a quantitative approach by collecting data through questionnaires to Gerai Taslim customers who have made transactions through e-commerce platforms. Assessment criteria include ease of use, product design and content, service quality, delivery speed, and transaction costs. Data were analyzed using validity, reliability, weighting, matrix normalization, and preference value calculations using the SAW method. The results showed that all instruments were declared valid and reliable. Based on the SAW calculation, Shopee obtained the highest preference value of 1,000, followed by Tokopedia at 0.907 and Lazada at 0.559. These results indicate that Shopee is the most optimal platform in supporting Gerai Taslim customer satisfaction. This research has implications as a basis for decision-making in determining more effective and targeted digital marketing strategies.